Shifting Logics: The Discourses of Turkish Political Elites on EU Accession. Issue 1 (2nd January 2016) - Balkır, Canan; Eylemer, Sedef
Abstract: The article compares the EU accession discourses, during the 2002, 2007 and 2011 elections, of Turkey's governing Justice and Development Party (AKP) with those of the two main opposition parties, the Republican People's Party (CHP) and the Nationalist Action Party (MHP), tracking the continuities and shifts in their discourses. In the light of Habermas's distinction between pragmatic, ethical and moral justifications, the discourses are analysed on the basis of three explanatory logics – interests, rights and identity – by means of a theoretically guided qualitative content analysis of the election manifestos of these three political parties. These logics, emerging and shifting in line with periodical dynamics, have been instrumental to varying degrees in the discourses of Turkey's political elites.